In Situ Characterization of Hfq Bacterial Amyloid: A Fourier-Transform Infrared Spectroscopy Study - Partouche, David (2019)
Hfq is a bacterial protein that regulates gene expression at the post-transcriptional level in Gram-negative bacteria. We have previously shown that Escherichia coli Hfq protein, and more precisely its C-terminal region (CTR), self-assembles into an amyloid-like structure in vitro. In the present work, we present evidence that Hfq unambiguously forms amyloid structures also in vivo. Taking into account the role of this protein in bacterial adaptation and virulence, our work opens possibilities to target Hfq amyloid self-assembly and cell location, with potential to block bacterial adaptation and treat infections.